2007
DOI: 10.1134/s199034130701004x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of optical counterparts of ultraluminous X-ray sources

Abstract: Abstract. Here we present the results of panoramic and long-slit observations of eight ULX nebular counterparts held with the 6m SAO telescope. In two ULXNe we detected for the first time signatures of high excitation ([O iii]λ5007 / Hβ > 5). Two of the ULXs were identified with young (T ∼ 5 − 10 M yr) massive star clusters. Four of the eight ULX Nebulae (ULXNe) show bright high-excitation lines. This requires existence of luminous (∼ 10 38 ÷ 10 40 ergs s −1 ) UV/EUV sources coinciding with the X-ray sources. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 50 publications
10
116
0
Order By: Relevance
“…Since the nuclei in our targets have X-ray luminosities much higher than typical ULXs, they are most likely of a different origin. Further evidence against the ULX scenario includes: (1) the BHs are expected to be supermassive given their host bulge properties (Liu et al 2010a); (2) the observed [O III] luminosities are significantly higher than those for ULXs (Abolmasov et al 2007); and (3) the X-ray point sources in our targets are nuclear given astrometric uncertainties, although ULXs could also live close to nuclear regions.…”
Section: X-ray Luminosity and Spectral Propertiesmentioning
confidence: 99%
“…Since the nuclei in our targets have X-ray luminosities much higher than typical ULXs, they are most likely of a different origin. Further evidence against the ULX scenario includes: (1) the BHs are expected to be supermassive given their host bulge properties (Liu et al 2010a); (2) the observed [O III] luminosities are significantly higher than those for ULXs (Abolmasov et al 2007); and (3) the X-ray point sources in our targets are nuclear given astrometric uncertainties, although ULXs could also live close to nuclear regions.…”
Section: X-ray Luminosity and Spectral Propertiesmentioning
confidence: 99%
“…Strong beaming, however, can be ruled out in some cases by observations of photo-ionised nebulae surrounding the ULXs because the observed line properties require luminosities comparable to the observed X-ray luminosities (Pakull & Mirioni 2003;Kaaret et al 2004;Abolmasov et al 2007;Kaaret & Corbel 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It was realised that an enhanced He IIλ 4686 line is common for many ULXNe [9,10] including even ULX bubbles [11,12]. The He II emission is often proposed to be a wind or atmospheric emission of the central object.…”
Section: Ulx Nebulaementioning
confidence: 99%
“…This result may appear to be the first detection of orbital motion for a ULX. Usually (see [11] and [7]) the He IIλ 4686 emission is narrow (FW HM 200 km s −1 ) but is emitted in the vicinity of the X-ray source therefore the best explanation is a compact HeIII-region.…”
Section: Ulx Nebulaementioning
confidence: 99%
See 1 more Smart Citation